Customer preferences on the car market in the Central Europe - Busheev, Artemii; Semenenko, Vadim; Procházka, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This thesis investigates the factors that affect the purchasing decision of consumers in Germany, Poland and Czech Republic. The thesis is done with the use of a questionnaire where the answers are analysed using exploratory factor analysis. The study reveals 6 latent factors for the German sample, and 5 latent factors for the Polish and Czech samples. The thesis shows that German consumers conceive the safety of the vehicle as the most important factor, however, Polish and Czech consumers have shown that they perceive the quality of the car compared to its price as the most important factor. The outcome of the analysis concludes the recommendations for the car makers on how the marketing strategy can be improved with these findings.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses